Effects of the combined use of a scissor-type knife and traction clip on endoscopic submucosal dissection of colorectal tumors: a propensity score-matched analysis - Inoue, Ken; Yoshida, Naohisa; Dohi, Osamu; Sugino, Satoshi; Matsumura, Shinya; Kitae, Hiroaki; Yasuda, Ritsu; Nakano, Takahiro; Terasaki, Kei; Hirose, Ryohei; Naito, Yuji; Murakami, Takaaki; Inada, Yutaka; Ogiso, Kiyoshi; Morinaga, Yukiko; Kishimoto, Mitsuo; Yoshito, Itoh (Endoscopy International Open, 2021)
Background and study aims This study evaluated the technical aspects of colorectal endoscopic submucosal dissection (ESD) with the Clutch Cutter (CC) (Fujifilm Co., Tokyo, Japan), a scissor-type knife, and the S-O clip (SO) as a traction clip, and compared the safety and efficacy to ESD using a needle-type knife.Patients and methods This was a single-center retrospective study. In Study 1, we evaluated 125 ESD patients: 60 using the SO and CC (SO group) and 65 using the CC (CC group). In Study 2, we evaluated 185 ESD patients: the CC group (N = 65) and 120 using the Flush knife BT-S (Flush group) (Fujifilm Co., Tokyo, Japan). In both studies, the clinicopathological features and therapeutic outcomes were compared using a propensity score-matched analysis.Results In 36 pairs of matched patients in Study 1, the rates of en bloc resection, R0 resection, perforation, and postoperative bleeding (POB) were 97.2 %, 88.9 %, 2.8 %, and 0 %, respectively, for the SO group and 100 %, 91.7 %, 0 %, and 0 % for the CC group (not significant). The mean procedure time for the SO group among less-experienced endoscopists was significantly shorter than in the CC group (42 vs. 65 minutes, P = 0.036). In 49 pairs of matched patients in Study 2, the rates of en bloc resection, R0 resection, perforation, and POB were 100 %, 95.8 %, 0 %, and 0 %, respectively, for the CC group and 98.0 %, 95.8 %, 0 %, and 2.0 % for the Flush group (not significant). The mean procedure time in the CC group among less-experienced endoscopists was significantly shorter than in the Flush group (52 vs. 67 minutes, P = 0.038).Conclusions CC and the combined use of CC and SO reduced colorectal ESD procedure time among less-experienced endoscopists.